Preparation method and application of sub-nanometer monodisperse copper cerium oxide catalyst
Patent Information
- Application Number
- CN202311801570.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-12-25
AI Technical Summary
该方法的存在的缺陷是:需要通过煅烧过程才能制备得结晶性良好的三价稀土掺杂二氧化铈纳米棒(轴向长度为50nm~100nm,径向长度为5~10nm),因此所制备的二氧化铈纳米颗粒易团聚,难以分散
[0057] The beneficial effects of this invention are as follows:
Smart Images

Figure HDA0004629006000000011 
Figure HDA0004629006000000012 
Figure HDA0004629006000000013
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanocatalyst technology; more specifically, to a method for preparing sub-nanometer-scale monodisperse copper cerium oxide catalysts and their application in photocatalytic carbon dioxide reduction. Background Technology
[0002] Photocatalytic carbon dioxide reduction driven by sunlight holds promise for mitigating the greenhouse effect. Due to its complex reduction pathway, the photoreduction products of carbon dioxide include carbon monoxide, methanol, methane, formaldehyde, formic acid, and multi-carbon molecules such as ethane, ethylene, ethanol, and acetic acid. Among these hydrocarbons, methane is an important clean fuel that can be used as an industrial feedstock to produce carbon black, H2, chloroform, and other valuable chemicals. Although the reduction of carbon dioxide to methane is more favorable in terms of reduction potential than the formation of CO and methanol, the process is kinetically more difficult because it requires the transfer of eight electrons to combine with multiple protons. Furthermore, the complex proton-electron transfer pathway easily branches into other unwanted products, significantly hindering the activity and selectivity of the photoreduction of carbon dioxide to methane.
[0003] Cerium dioxide has Ce2O3 (Ce) 3+ ) and CeO2 (Ce 4+ CeO2 has two stable oxidation states. In an oxygen-deficient environment, CeO2 forms Ce2O3 while simultaneously generating oxygen vacancies, which are then restored in an oxygen-rich environment. 3+ / Ce 4+ The redox properties of cerium dioxide give it excellent oxygen storage capacity, making it widely used in catalysis. Sub-nanometer-sized cerium dioxide can provide an ultra-high proportion of surface-coordinated unsaturated Ce atoms, which, as active sites, can generate active intermediates, helping to improve the conversion rate of carbon dioxide to methane. Furthermore, positively charged copper-doped cerium dioxide can stabilize the cubic fluorite structure of cerium dioxide, further enhancing its oxygen storage capacity and promoting the selective photocatalytic reduction of carbon dioxide to methane. Well-modified surface-sized copper-cerium oxides can be transparently dispersed in a liquid medium, allowing the catalyst to be uniformly loaded onto the support. The highly dispersed and homogeneous active centers ensure that the catalyst retains high selectivity and activity in the reaction system while also being easily separated and recovered.
[0004] Existing technologies for preparing cerium dioxide nanoparticles, such as Chinese patent CN116966911A, disclose a method for preparing a trivalent rare earth-doped cerium dioxide-supported metal catalyst. This method involves adding a trivalent rare earth salt to a cerium salt to incorporate the trivalent rare earth into cerium dioxide, then loading a metal catalyst precursor onto the surface of the trivalent rare earth-doped cerium dioxide and calcining it once. The drawback of this method is that a calcination process is required to prepare well-crystallized trivalent rare earth-doped cerium dioxide nanorods (axial length 50 nm–100 nm, radial length 5–10 nm), resulting in cerium dioxide nanoparticles that are prone to agglomeration and difficult to disperse. Summary of the Invention
[0005] The first technical problem to be solved by this invention is to provide a sub-nanometer-scale monodisperse copper-cerium oxide catalyst. The sub-nanometer-scale monodisperse copper-cerium oxide catalyst prepared by this invention has sub-nanometer-scale copper-cerium oxide particles that are easily dispersed in a liquid medium, with a solid content of 0.005 wt.% to 60 wt.%; the copper-cerium oxide particles have extremely small particle sizes, with a one-dimensional size of 0.5 to 3 nm; it exhibits monodispersity, uniform particle size distribution, and good dispersibility; the product has high permeability, high purity, and high stability, remaining transparent and without sedimentation even after standing for ≥24 months.
[0006] To solve the first technical problem mentioned above, the present invention adopts the following technical solution:
[0007] A sub-nanometer monodisperse copper-cerium oxide catalyst dispersion comprises sub-nanometer monodisperse copper-cerium oxide particles and a liquid medium; the sub-nanometer copper-cerium oxide is formed by uniformly distributing copper elements within cerium dioxide particles, the surface of the sub-nanometer monodisperse copper-cerium oxide particles is coated with a surface modifier layer, and the nano-cerium dioxide particles coated with a surfactant layer are uniformly dispersed in the liquid medium to form a transparent dispersion.
[0008] Preferably, the solid content of sub-nanometer copper cerium oxide in the transparent dispersion is 0.005 wt.% to 60 wt.%, and the one-dimensional size of the sub-nanometer copper cerium oxide particles is 0.5 nm to 3 nm.
[0009] Preferably, the surface modifier layer comprises one or more of the following substances: butyric acid, octanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, oleic acid, linoleic acid, oleylamine, sodium oleate, sodium silicate, sodium stearate, [3-(methacryloyloxy)propyl]trimethoxysilane (KH570), γ-glycidyl etheroxypropyltrimethoxysilane (KH560), (3-aminopropyl)triethoxysilane (KH550), (3-mercaptopropyl)trimethoxysilane, sodium dodecyl sulfate, hexadecyl ammonium bromide, Tween-80, polyethylene glycol-200, polyethylene glycol-4000, polyethylene glycol-10000, trimethyloxonium tetrafluoroborate, triethyloxonium tetrafluoroborate, nitrosotetrafluoroborate, tribenzylcarbium tetrafluoroborate, and ammonium fluoroborate.
[0010] Preferably, the liquid medium comprises one or more of the following substances: formamide, N,N-dimethylformamide, methanol, ethanol, ethylene glycol, acetonitrile, dimethyl sulfoxide, tetrahydrofuran, toluene, benzene, benzyl alcohol, cyclohexane, n-hexane, n-heptane, petroleum ether (30-60°C), petroleum ether (60-90°C), dichloromethane, chloroform, white oil, naphtha, castor oil, diesel oil, methyl isobutyl ketone, methyl methacrylate, and 3-phenoxybenzyl acrylate.
[0011] To address the second technical problem mentioned above, this invention provides a method for preparing a sub-nanometer-scale monodisperse copper-cerium oxide catalyst dispersion, comprising the following steps:
[0012] 1) Prepare a cerium source solution by adding a cerium source to water, an organic solvent, or a mixture of water and an organic solvent;
[0013] 2) Prepare an alkali source solution by adding an alkali source to water, an organic solvent, or a mixture of water and an organic solvent;
[0014] 3) Prepare a surface modifier solution by adding a surface modifier to water, an organic solvent, or a mixture of water and an organic solvent;
[0015] 4) Mix the cerium source solution from step 1) with the alkali source solution from step 2), and continue the reaction after mixing;
[0016] 5) Mix the surface modifier solution with the mixture from step 4), continue the modification reaction after mixing, and then perform solid-liquid separation. Wash and dry the separated cerium dioxide solid.
[0017] 6) Using water, organic solvent, or a mixture of water and organic solvent as the dispersed phase, the washed and dried cerium dioxide solid can be transparently dispersed in the dispersed phase to obtain a transparent cerium dioxide dispersion.
[0018] 7) Prepare a copper source solution by adding a copper source to water, an organic solvent, or a mixture of water and an organic solvent.
[0019] 8) Mix the transparent cerium dioxide dispersion from step 6) with the copper source solution from step 7) and carry out a solvothermal reaction. After the reaction, perform solid-liquid separation, wash and dry the separated copper cerium oxide solid, and disperse the washed and dried copper cerium oxide solid in a liquid medium to obtain the product sub-nanometer monodisperse copper cerium oxide catalyst dispersion.
[0020] As a further improvement to the technical solution, in step 1), the cerium source is selected from one or more of the following substances: cerium fluoride, cerium iodide, cerium bromide, anhydrous cerium sulfate, cerium sulfate tetrahydrate, anhydrous cerium chloride, cerium chloride heptahydrate, cerium nitrate hexahydrate, cerium oxalate hydrate, cerium(III) carbonate hydrate, and cerium(III) acetate hydrate.
[0021] Preferably, in step 1), the organic solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol, glycerol, benzyl alcohol, toluene, tetrahydrofuran, dichloromethane, chloroform, N,N-dimethylformamide, and dimethyl sulfoxide; the ratio of water to organic solvent in the solvent is arbitrary.
[0022] In step 1), the concentration of the cerium source solution is 0.01 wt.% to 60 wt%.
[0023] Preferably, in step 1), the concentration of the cerium source solution is 0.1 wt.% to 50 wt.%.
[0024] As a further improvement to the technical solution, in step 2), the alkali source is selected from one or more of the following substances: sodium hydroxide, potassium hydroxide, calcium hydroxide, ammonia, tetramethylammonium hydroxide, tetraethylammonium hydroxide, triethylamine, and triethanolamine.
[0025] Preferably, in step 2), the organic solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol, glycerol, benzyl alcohol, toluene, tetrahydrofuran, dichloromethane, chloroform, N,N-dimethylformamide, dimethyl sulfoxide, and methyl isobutyl ketone; the ratio of water to organic solvent in the solvent is arbitrary; the ratio of water to organic solvent in the solvent is arbitrary.
[0026] In step 2), the concentration of the alkaline source solution is 0.1 wt.% to 50 wt.%.
[0027] Preferably, in step 2), the concentration of the alkaline source solution is 0.5 wt.% to 40 wt.%.
[0028] As a further improvement to the technical solution, in step 3), the surface modifier is selected from one or more of the following substances: butyric acid, octanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, oleic acid, linoleic acid, oleylamine, sodium oleate, sodium arsenate, sodium stearate, [3-(methacryloyloxy)propyl]trimethoxysilane (KH570), γ-glycidoxypropyltrimethoxysilane (KH560), (3-aminopropyl)triethoxysilane (KH550), (3-mercaptopropyl)trimethoxysilane, sodium dodecyl sulfate, hexadecyl ammonium bromide, Tween-80, polyethylene glycol-200, polyethylene glycol-4000, polyethylene glycol-10000, trimethyloxonium tetrafluoroborate, triethyloxonium tetrafluoroborate, nitrosotetrafluoroborate, tribenzylcarbium tetrafluoroborate, ammonium fluoroborate;
[0029] Preferably, in step 3), the organic solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol, glycerol, benzyl alcohol, toluene, tetrahydrofuran, dichloromethane, chloroform, N,N-dimethylformamide, dimethyl sulfoxide, and methyl isobutyl ketone; the ratio of water to organic solvent in the solvent is arbitrary.
[0030] In step 3), the concentration of the surface modifier solution is 0.1 wt.% to 80 wt.%.
[0031] Preferably, in step 3), the concentration of the surfactant solution is 0.5 wt.% to 40 wt.%.
[0032] As a further improvement to the technical solution, in step 4), the mixing method of the cerium source solution and the alkali source solution is as follows: the cerium source solution is added to the alkali source solution at a certain flow rate, or the alkali source solution is added to the cerium source solution at a certain flow rate; the flow rate is 0.01~100L / min / mol Ce element; the stirring rate is 200~800r / min.
[0033] In step 4), the reaction temperature is 10–150°C, and the reaction time is 0–3 h.
[0034] Preferably, the reaction temperature is 15–95°C and the reaction time is 0–2.5 h.
[0035] As a further improvement to the technical solution, in step 5), the mixing method of the mixture and surfactant solution in step 4) is as follows: the surface modifier solution is added to the mixture in step 4) at a certain flow rate; the flow rate is 0.03 to 90 L / min / mol Ce element; the stirring rate is 200 to 800 r / min; and the volume ratio of the mixture to the surfactant solution is 0.1 to 50:1.
[0036] The liquid medium used for washing is selected from one or more of the following substances: methanol, ethanol, isopropanol, toluene, cyclohexane, n-hexane, acetone, benzyl alcohol, tetrahydrofuran, dichloromethane, and trichloromethane; the washing method is one or more of rinsing, filtration (vacuum filtration or pressure filtration, ultrafiltration, nanofiltration), dialysis, and centrifugation; the number of washing cycles is 2 to 5; the drying method is one or more of freeze drying, vacuum drying, atmospheric pressure evaporation, rotary vacuum evaporation, forced air drying, infrared irradiation, and spray drying.
[0037] In step 5), the modification reaction temperature is 10–180°C, the modification reaction time is 15 min–6 h, and the drying temperature is -10–150°C, the drying time is 5 min–48 h.
[0038] Preferably, in step 5), the modification reaction temperature is 10–80°C; the modification reaction time is 30 min–2.5 h; the drying temperature is -5–120°C; and the drying time is 5 min–36 h.
[0039] As a further improvement to the technical solution, in step 6), the organic solvent is selected from one or more of the following substances: formamide, N,N-dimethylformamide, methanol, ethanol, ethylene glycol, acetonitrile, dimethyl sulfoxide, tetrahydrofuran, toluene, benzene, benzyl alcohol, cyclohexane, n-hexane, n-heptane, petroleum ether (30-60℃), petroleum ether (60-90℃), dichloromethane, chloroform, white oil, naphtha, castor oil, diesel oil, methyl isobutyl ketone, methyl methacrylate, 3-phenoxybenzyl acrylate;
[0040] In step 6), the solid content of the obtained cerium dioxide dispersion is 0.005 wt.% to 60 wt.%.
[0041] Preferably, the solid content of the obtained cerium dioxide dispersion is 0.5 wt.% to 60 wt.%.
[0042] As a further improvement to the technical solution, in step 7), the copper source is selected from one or more of the following substances: copper gluconate, copper acetylacetonate, copper fluoroborate, copper citrate, copper acetate monohydrate, copper isooctanoate, anhydrous copper acetate, basic copper carbonate, copper tartrate(II) hydrate, copper oxalate, copper acetate monohydrate, butyrate, copper stearate, anhydrous copper sulfate, copper sulfate pentahydrate, basic copper sulfate, anhydrous copper chloride, copper chloride dihydrate, and copper nitrate trihydrate; the organic solvent is selected from one or more of the following substances: oleic acid, linoleic acid, oleylamine, methanol, ethanol, isopropanol, toluene, benzyl alcohol, cyclohexane, n-hexane, and 1,2-butanediol; the ratio of water to organic solvent in the solvent is arbitrary; the volume ratio of copper source solution to cerium source solution is 0.01 to 50:1;
[0043] In step 7), the concentration of the copper source solution is 0.01 wt.% to 20 wt.%.
[0044] Preferably, in step 7), the concentration of the copper source solution is 0.05 wt.% to 18 wt.%.
[0045] As a further improvement to the technical solution, in step 8), the mixing method of the cerium dioxide transparent dispersion and the copper source solution is as follows: the cerium dioxide transparent dispersion is added to the copper source solution at a certain flow rate; the flow rate is 0.01–100 L / min / mol Ce element; the stirring rate is 0–800 r / min; the separation and washing methods are one or more of rinsing, filtration (vacuum filtration or pressure filtration, ultrafiltration, nanofiltration), dialysis, and centrifugation; the liquid phase medium used for washing is selected from one or more of the following substances: methanol, ethanol, isopropanol, toluene, cyclohexane, n-hexane, acetone, benzyl alcohol, tetrahydrofuran, dichloromethane, and trichloromethane; the number of washing times is 2–5 times; the drying method is freeze drying, vacuum drying, atmospheric pressure evaporation, rotary vacuum evaporation, forced air drying, and infrared drying. One or more of irradiation and spray drying; the liquid medium is selected from one or more of the following substances: formamide, N,N-dimethylformamide, methanol, ethanol, ethylene glycol, acetonitrile, dimethyl sulfoxide, tetrahydrofuran, toluene, benzene, benzyl alcohol, cyclohexane, n-hexane, n-heptane, petroleum ether (30-60℃), petroleum ether (60-90℃), dichloromethane, chloroform, white oil, naphtha, castor oil, diesel oil, methyl isobutyl ketone, methyl methacrylate, 3-phenoxybenzyl acrylate;
[0046] In step 8), the molar ratio of cerium dioxide to Cu:Ce in the copper source is 0.0001–3:1; the solvothermal reaction temperature is 80–260℃; the solvothermal time is 2 h–96 h; the drying temperature is -10–150℃; and the drying time is 5 min–48 h. The concentration of the obtained sub-nanometer monodisperse copper-cerium oxide catalyst transparent dispersion is 0.005 wt.%–60 wt.%.
[0047] Preferably, in step 8), the molar ratio of cerium dioxide to Cu:Ce in the copper source is 0.005–2.7:1; the volume ratio of the copper source solution to the cerium source solution is 0.01–40:1; the solvothermal reaction temperature is 120–250°C; the solvothermal time is 2–72 h; the drying temperature is -5–120°C; the drying time is 5 min–36 h; and the concentration of the obtained sub-nanometer monodisperse copper-cerium oxide catalyst transparent dispersion is 0.5 wt.%–60 wt.%.
[0048] The third technical problem this invention aims to solve is to provide an application of a sub-nanometer-scale monodisperse copper-cerium oxide catalyst as a photocatalytic carbon dioxide reduction catalyst; the photocatalytic carbon dioxide reduction system can use either a gas-solid mode or a liquid-solid mode. In the gas-solid mode, the prepared sub-nanometer-scale monodisperse copper-cerium oxide catalyst nano-dispersion is loaded onto a support, and the surfactant layer encapsulated by the nano-copper-cerium oxide catalyst is removed by ultraviolet ozone photo-cleaning. Deionized water is used as a sacrificial agent, and carbon dioxide is used as the reactant for visible light irradiation reaction. In the liquid-solid mode, the sub-nanometer-scale monodisperse copper-cerium oxide catalyst nano-dispersion is directly added to the reaction system, a sacrificial agent is added, and carbon dioxide is used as the reactant for visible light irradiation reaction.
[0049] Preferably, the carrier in the gas-solid mode is one or more of ITO glass, FTO glass, ordinary glass, hydrophilic carbon cloth, and hydrophobic carbon cloth;
[0050] Preferably, the loading method in the gas-solid mode is one or more of the following: impregnation, spin coating, scraping, and spraying.
[0051] Preferably, the photocatalytic carbon dioxide reduction products in the gas-solid mode are one or more of carbon monoxide, hydrogen, methane, ethylene, and ethane.
[0052] Preferably, the sacrificial agent in the liquid-solid mode is one or more of triethanolamine, triethylamine, sodium N,N-dimethylformamide sulfide, sodium sulfite, and lactic acid;
[0053] Preferably, the photocatalytic carbon dioxide reduction products in the liquid-solid mode are one or more of carbon monoxide, hydrogen, methane, ethylene, ethane, formic acid, acetic acid, methanol, and ethanol.
[0054] Any range described in this invention includes the endpoint, any value between the endpoints, and any subrange consisting of the endpoint or any value between the endpoints.
[0055] Unless otherwise specified, all raw materials used in this invention can be obtained commercially, and the equipment used in this invention can be conventional equipment in the relevant field or refer to existing technology in the relevant field.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] The beneficial effects of this invention are as follows:
[0058] 1) The sub-nanometer monodisperse copper cerium oxide catalyst prepared by the present invention is wherein the sub-nanometer monodisperse copper cerium oxide is readily and transparently dispersed in a liquid solvent, and the solid content is 0.005 wt.% to 60 wt.%.
[0059] 2) Copper cerium oxide crystals have small grain size, with a one-dimensional size of 0.5–3 nm; they are monodisperse, with uniform particle size distribution and good dispersibility;
[0060] 3) This product has high transmittance, high purity, and high stability; it remains transparent and shows no sedimentation even after standing for ≥6 months.
[0061] 4) This product has excellent photocatalytic reduction performance of carbon dioxide. Attached Figure Description
[0062] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0063] Figure 1 This image shows a photograph of the cerium dioxide obtained in step 6) of Embodiment 1 of the present invention.
[0064] Figure 2 This image shows a photograph of the copper cerium oxide obtained in step 8) of Embodiment 1 of the present invention.
[0065] Figure 3 The transmission electron microscope (TEM) image and corresponding particle size distribution diagram of the copper cerium oxide obtained in step 8) of Example 1 of the present invention are shown.
[0066] Figure 4 The X-ray diffraction (XRD) patterns of cerium dioxide obtained in step 6) and copper cerium oxide obtained in step 8) of Embodiment 1 of the present invention are shown.
[0067] Figure 5 The X-ray energy dispersive X-ray spectrum (EDX) of the copper cerium oxide obtained in step 8) of Example 1 of the present invention is shown.
[0068] Figure 6 A physical diagram of an apparatus (applicable to gas-solid mode and liquid-solid mode) for photocatalytic carbon dioxide reduction using the copper-cerium oxide catalyst obtained in step 8) of Embodiment 1 of the present invention is shown.
[0069] Figure 7 The experimental results of photocatalytic carbon dioxide reduction using a gas-solid method are shown in Example 1 of the present invention.
[0070] Figure 8 This image shows a photograph of the cerium dioxide obtained in step 6) of Embodiment 2 of the present invention.
[0071] Figure 9 A photograph of the copper cerium oxide obtained in step 8) of Embodiment 2 of the present invention is shown;
[0072] Figure 10 The experimental results of photocatalytic carbon dioxide reduction using the liquid-solid method are shown in Example 2 of the present invention.
[0073] Figure 11Transmission electron microscope images and corresponding physical images of the zirconium dioxide and cuprous oxide nanoparticle mixture obtained in Comparative Example 2 of the present invention are shown. Detailed Implementation
[0074] To more clearly illustrate the present invention, the following description, in conjunction with preferred embodiments, further clarifies the invention. Those skilled in the art should understand that the specific descriptions below are illustrative rather than restrictive, and should not be construed as limiting the scope of protection of the present invention.
[0075] As one aspect of the present invention, a sub-nanometer-scale monodisperse copper-cerium oxide catalyst is provided, comprising sub-nanometer-scale monodisperse copper-cerium oxide particles and a liquid medium; the surface of the sub-nanometer-scale monodisperse copper-cerium oxide particles is coated with a surfactant layer, and the sub-nanometer-scale monodisperse copper-cerium oxide particles coated with the surfactant layer are uniformly dispersed in the liquid medium to form a transparent dispersion.
[0076] According to certain embodiments of the present invention, the solid content of nano-cerium dioxide in the transparent dispersion is 0.005 wt.% to 60 wt.%, or 0.01 wt.% to 60 wt.%, or 0.02 wt.% to 60 wt.%, or 0.05 wt.% to 60 wt.%, or 0.1 wt.% to 60 wt.%, or 0.5 wt.% to 60 wt.%, or 1 wt.% to 60 wt.%, or 2 wt.% to 60 wt.%, or 5 wt.% to 60 wt.%, or 8 wt.% to 60 wt.%, or 10 wt.% to 60 wt.%. The one-dimensional size of the sub-nanometer monodisperse copper cerium oxide particles is 0.5–3 nm, and the particle size is 10 wt.% to 50 wt.%, 10 wt.% to 45 wt.%, 10 wt.% to 40 wt.%, 10 wt.% to 35 wt.%, 10 wt.% to 30 wt.%, 10 wt.% to 25 wt.%, 10 wt.% to 20 wt.%, 10 wt.% to 15 wt.%, 15 wt.% to 55 wt.%, 20 wt.% to 50 wt.%, or 25 wt.% to 40 wt.%.
[0077] According to certain embodiments of the present invention, the surfactant layer comprises one or more of the following substances: butyric acid, octanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, oleic acid, linoleic acid, oleylamine, sodium oleate, sodium arsenate, sodium stearate, [3-(methacryloyloxy)propyl]trimethoxysilane (KH570), γ-glycidyl etheroxypropyltrimethoxysilane (KH560), (3-aminopropyl)triethoxysilane (KH550), (3-mercaptopropyl)trimethoxysilane, sodium dodecyl sulfate, hexadecyl ammonium bromide, Tween-80, polyethylene glycol-200, polyethylene glycol-4000, polyethylene glycol-10000, trimethyloxonium tetrafluoroborate, triethyloxonium tetrafluoroborate, nitrosotetrafluoroborate, tribenzylcarbium tetrafluoroborate, and ammonium fluoroborate.
[0078] According to certain embodiments of the present invention, the liquid medium comprises one or more of the following substances: formamide, N,N-dimethylformamide, methanol, ethanol, ethylene glycol, acetonitrile, dimethyl sulfoxide, tetrahydrofuran, toluene, benzene, benzyl alcohol, cyclohexane, n-hexane, n-heptane, petroleum ether (30-60°C), petroleum ether (60-90°C), dichloromethane, chloroform, white oil, naphtha, castor oil, diesel oil, methyl isobutyl ketone, methyl methacrylate, and 3-phenoxybenzyl acrylate.
[0079] As another aspect of the present invention, a method for preparing a sub-nanometer-scale monodisperse copper-cerium oxide catalyst includes the following steps:
[0080] 1) Prepare a cerium source solution by adding a cerium source to water, an organic solvent, or a mixture of water and an organic solvent;
[0081] 2) Prepare an alkali source solution by adding an alkali source to water, an organic solvent, or a mixture of water and an organic solvent;
[0082] 3) Prepare a surface modifier solution by adding a surface modifier to water, an organic solvent, or a mixture of water and an organic solvent;
[0083] 4) Mix the cerium source solution with the alkali source solution, and continue the reaction after mixing;
[0084] 5) Mix the surface modifier solution with the mixture from step 4), continue the modification reaction after mixing, and then perform solid-liquid separation. Wash and dry the separated cerium dioxide solid.
[0085] 6) Using water, organic solvent, or a mixture of water and organic solvent as the dispersed phase, the washed and dried cerium dioxide solid can be transparently dispersed in the dispersed phase to obtain a transparent cerium dioxide dispersion.
[0086] 7) Prepare a copper source solution by adding a copper source to water, an organic solvent, or a mixture of water and an organic solvent.
[0087] 8) Mix the transparent dispersion of cerium dioxide with the copper source solution and carry out a solvothermal reaction. After the reaction, perform solid-liquid separation, wash and dry the separated copper cerium oxide solid. The washed and dried copper cerium oxide solid can be transparently dispersed in the liquid solvent to obtain the product, a sub-nanometer monodisperse copper cerium oxide catalyst.
[0088] The preparation method proposed in this invention produces monodisperse, sub-nanometer-sized copper-cerium oxide particles with a particle size ranging from 0.5 to 3 nm. These particles can be transparently and monodispersed in a liquid medium with extremely high solid content (0.005 wt.% to 60 wt.%) and can remain stable for a long time. They are among the smallest copper-cerium oxide particles reported to date. The sub-nanometer-sized copper-cerium oxide particles prepared in this invention can be well transparently and monodispersed in a liquid medium to form a copper-cerium oxide dispersion. The sub-nanometer-sized monodisperse copper-cerium oxide catalyst nanodispersion is supported on a carrier, and the surfactant layer encapsulated by the nano-copper-cerium oxide catalyst is removed by irradiation with an ultraviolet ozone photocatalyst, exhibiting excellent photocatalytic activity.
[0089] According to certain embodiments of the present invention, in step 1), the cerium source is selected from one or more of the following substances: cerium fluoride, cerium iodide, cerium bromide, anhydrous cerium sulfate, cerium sulfate tetrahydrate, anhydrous cerium chloride, cerium chloride heptahydrate, cerium nitrate hexahydrate, cerium oxalate hydrate, cerium(III) carbonate hydrate, and cerium(III) acetate hydrate; the organic solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol, glycerol, benzyl alcohol, toluene, tetrahydrofuran, dichloromethane, chloroform, N,N-dimethylformamide, and dimethyl sulfoxide; the ratio of water to organic solvent in the solvent is arbitrary.
[0090] In step 1), the concentration of the cerium source solution is 0.01 wt.% to 60 wt%.
[0091] Preferably, in step 1), the concentration of the cerium source solution is 0.1 wt.% to 50 wt.%.
[0092] According to certain embodiments of the present invention, in step 2), the alkali source is selected from one or more of the following substances: sodium hydroxide, potassium hydroxide, calcium hydroxide, ammonia, tetramethylammonium hydroxide, tetraethylammonium hydroxide, triethylamine, triethanolamine; the organic solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol, glycerol, benzyl alcohol, toluene, tetrahydrofuran, dichloromethane, chloroform, N,N-dimethylformamide, dimethyl sulfoxide, methyl isobutyl ketone; the ratio of water to organic solvent in the solvent is arbitrary; the ratio of water to organic solvent in the solvent is arbitrary.
[0093] In step 2), the concentration of the alkali source solution is 0.1 wt.% to 50 wt.%; the volume ratio of the alkali source solution to the cerium source solution is 0.01 to 6:1.
[0094] Preferably, in step 2), the concentration of the alkali source solution is 0.5 wt.% to 40 wt.%; the volume ratio of the alkali source solution to the cerium source solution is 0.02 to 5:1.
[0095] According to certain embodiments of the present invention, in step 3), the surface modifier is selected from one or more of the following substances: butyric acid, octanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, oleic acid, linoleic acid, oleylamine, sodium oleate, sodium ceroxide, sodium stearate, [3-(methacryloyloxy)propyl]trimethoxysilane (KH570), γ-glycidyl etheroxypropyltrimethoxysilane (KH560), (3-aminopropyl)triethoxysilane (KH550), (3-mercaptopropyl)trimethoxysilane, sodium dodecyl sulfate, hexadecyl bromide The organic solvent is selected from one or more of the following substances: ammonium, Tween-80, polyethylene glycol-200, polyethylene glycol-4000, polyethylene glycol-10000, trimethyloxonium tetrafluoroborate, triethyloxonium tetrafluoroborate, nitrosotetrafluoroborate, tribenzylcarbium tetrafluoroborate, and ammonium fluoroborate; the organic solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol, glycerol, benzyl alcohol, toluene, tetrahydrofuran, dichloromethane, chloroform, N,N-dimethylformamide, dimethyl sulfoxide, and methyl isobutyl ketone; the ratio of water to organic solvent in the solvent is arbitrary.
[0096] In step 3), the concentration of the surface modifier solution is 0.1 wt.% to 80 wt.%; the volume ratio of the surface modifier solution to the cerium source solution is 0.001 to 50:1.
[0097] Preferably, in step 3), the concentration of the surfactant solution is 0.5 wt.% to 40 wt.%; the volume ratio of the surface modifier solution to the cerium source solution is 0.001 to 45:1.
[0098] According to certain embodiments of the present invention, in step 4), the mixing method of the cerium source solution and the alkali source solution is as follows: the cerium source solution is added to the alkali source solution at a certain flow rate, or the alkali source solution is added to the cerium source solution at a certain flow rate; the flow rate is 0.01 to 100 L / min / mol Ce element; the stirring rate is 200 to 800 r / min;
[0099] In step 4), the reaction temperature is 10–150°C, and the reaction time is 0–3 h.
[0100] Preferably, the reaction temperature is 15–95°C and the reaction time is 0–2.5 h.
[0101] According to certain embodiments of the present invention, in step 5), the mixing method of the mixture and surfactant solution in step 4) is as follows: the surface modifier solution is added to the mixture in step 4) at a certain flow rate; the flow rate is 0.03-90 L / min / mol Ce element; the stirring rate is 200-800 r / min; the washing method is one or more of rinsing, filtration (vacuum filtration or pressure filtration, ultrafiltration, nanofiltration), dialysis, and centrifugation; the liquid phase medium used for washing is selected from one or more of the following substances: methanol, ethanol, isopropanol, toluene, cyclohexane, n-hexane, acetone, benzyl alcohol, tetrahydrofuran, dichloromethane, and trichloromethane; the number of washing times is 2-5 times; the drying method is one or more of freeze drying, vacuum drying, atmospheric pressure evaporation, rotary vacuum evaporation, forced air drying, infrared irradiation, and spray drying.
[0102] In step 5), the modification reaction temperature is 10–180°C, the modification reaction time is 15 min–6 h, and the drying temperature is -10–150°C, the drying time is 5 min–48 h.
[0103] Preferably, in step 5), the modification reaction temperature is 10–80°C; the modification reaction time is 30 min–2.5 h; the drying temperature is -5–120°C; and the drying time is 5 min–36 h.
[0104] According to certain embodiments of the present invention, in step 6), the organic solvent is selected from one or more of the following substances: formamide, N,N-dimethylformamide, methanol, ethanol, ethylene glycol, acetonitrile, dimethyl sulfoxide, tetrahydrofuran, toluene, benzene, benzyl alcohol, cyclohexane, n-hexane, n-heptane, petroleum ether (30-60°C), petroleum ether (60-90°C), dichloromethane, chloroform, white oil, naphtha, castor oil, diesel oil, methyl isobutyl ketone, methyl methacrylate, 3-phenoxybenzyl acrylate;
[0105] In step 6), the solid content of the obtained cerium dioxide dispersion is 0.005 wt.% to 60 wt.%.
[0106] Preferably, the solid content of the obtained cerium dioxide dispersion is 0.5 wt.% to 60 wt.%.
[0107] According to certain preferred embodiments of the present invention, in step 7), the copper source is selected from one or more of the following substances: copper gluconate, copper acetylacetonate, copper fluoroborate, copper citrate, copper acetate monohydrate, copper isooctanoate, anhydrous copper acetate, basic copper carbonate, copper(II) tartrate hydrate, copper oxalate, copper acetate monohydrate, butyrate, copper stearate, anhydrous copper sulfate, copper sulfate pentahydrate, basic copper sulfate, anhydrous copper chloride, copper chloride dihydrate, and copper nitrate trihydrate; the organic solvent is selected from one or more of the following substances: oleic acid, linoleic acid, oleylamine, methanol, ethanol, isopropanol, toluene, benzyl alcohol, cyclohexane, n-hexane, and 1,2-butanediol; the ratio of water to organic solvent in the solvent is arbitrary.
[0108] In step 7), the concentration of the copper source solution is 0.01 wt.% to 20 wt.%.
[0109] Preferably, in step 7), the concentration of the copper source solution is 0.05 wt.% to 18 wt.%.
[0110] According to certain preferred embodiments of the present invention, in step 8), the mixing method of the cerium dioxide transparent dispersion and the copper source solution is as follows: the cerium dioxide transparent dispersion is added to the copper source solution at a certain flow rate; the flow rate is 0.01-100 L / min / mol Ce element; the stirring rate is 0-800 r / min; the separation and washing method is one or more of rinsing, filtration (vacuum filtration or pressure filtration, ultrafiltration, nanofiltration), dialysis, and centrifugation; the liquid phase medium used for washing is selected from one or more of the following substances: methanol, ethanol, isopropanol, toluene, cyclohexane, n-hexane, acetone, benzyl alcohol, tetrahydrofuran, dichloromethane, and trichloromethane; the number of washing times is 2-5 times; the drying method is freeze drying, vacuum drying, atmospheric pressure evaporation, rotary vacuum evaporation, forced air drying, and infrared drying. One or more of irradiation and spray drying; the liquid medium is selected from one or more of the following substances: formamide, N,N-dimethylformamide, methanol, ethanol, ethylene glycol, acetonitrile, dimethyl sulfoxide, tetrahydrofuran, toluene, benzene, benzyl alcohol, cyclohexane, n-hexane, n-heptane, petroleum ether (30-60℃), petroleum ether (60-90℃), dichloromethane, chloroform, white oil, naphtha, castor oil, diesel oil, methyl isobutyl ketone, methyl methacrylate, 3-phenoxybenzyl acrylate;
[0111] In step 8), the atomic ratio of cerium dioxide to Cu:Ce in the copper source is 0.0001–3:1; the solvothermal reaction temperature is 80–260℃; the solvothermal time is 2 h–96 h; the drying temperature is -10–150℃; and the drying time is 5 min–48 h. The concentration of the obtained sub-nanometer monodisperse copper-cerium oxide catalyst transparent dispersion is 0.005 wt.%–60 wt.%.
[0112] Preferably, in step 8), the atomic ratio of cerium dioxide to Cu:Ce in the copper source is 0.005–2.7:1; the volume ratio of the copper source solution to the cerium source solution is 0.01–40:1; the solvothermal reaction temperature is 120–250°C; the solvothermal time is 2–72 h; the drying temperature is -5–120°C; the drying time is 5 min–36 h; and the concentration of the obtained sub-nanometer monodisperse copper-cerium oxide catalyst transparent dispersion is 0.5 wt.%–60 wt.%.
[0113] In another aspect of the present invention, the sub-nanometer-scale monodisperse copper-cerium oxide catalyst prepared above is used as a photocatalytic carbon dioxide reduction catalyst; the photocatalytic carbon dioxide reduction system can be used in a gas-solid mode or a liquid-solid mode. In the gas-solid mode, the prepared sub-nanometer-scale monodisperse copper-cerium oxide catalyst nanodispersion is loaded onto a support, and the surfactant layer encapsulated on the nano-copper-cerium oxide catalyst is removed by ultraviolet ozone photo-cleaning, using deionized water as a sacrificial agent and carbon dioxide as a reactant; in the liquid-solid mode, the sub-nanometer-scale monodisperse copper-cerium oxide catalyst nanodispersion is directly added to the reaction system, with a sacrificial agent added, and carbon dioxide as a reactant.
[0114] Preferably, the carrier in the gas-solid mode is one or more of ITO glass, FTO glass, ordinary glass, hydrophilic carbon cloth, and hydrophobic carbon cloth;
[0115] Preferably, the loading method in the gas-solid mode is one or more of the following: impregnation, spin coating, scraping, and spraying.
[0116] Preferably, the photocatalytic carbon dioxide reduction products in the gas-solid mode are one or more of carbon monoxide, hydrogen, methane, ethylene, and ethane.
[0117] Preferably, the sacrificial agent in the liquid-solid mode is one or more of triethanolamine, triethylamine, sodium N,N-dimethylformamide sulfide, sodium sulfite, and lactic acid;
[0118] Preferably, the photocatalytic carbon dioxide reduction products in the liquid-solid mode are one or more of carbon monoxide, hydrogen, methane, ethylene, ethane, formic acid, acetic acid, methanol, and ethanol.
[0119] The preparation process parameters of this invention constitute an organic whole technical solution, thereby obtaining a sub-nanometer monodisperse copper cerium oxide catalyst with a solid content of 0.005 wt.% to 60 wt.% and a one-dimensional size of 0.5 to 3 nm. It has monodispersity, uniform particle size distribution, good dispersibility, and no sedimentation after standing for ≥24 months.
[0120] Example 1
[0121] A method for preparing a sub-nanometer-scale monodisperse copper-cerium oxide catalyst includes the following steps:
[0122] 1) Dissolve 8.86 g of cerium sulfate tetrahydrate in a mixture of 30 mL of dimethyl sulfoxide, 30 mL of ethanol and 60 mL of deionized water to prepare a cerium source solution;
[0123] 2) Dissolve 0.4 mL of tetramethylammonium hydroxide in a mixture of 45 mL of ethylene glycol and 90 mL of deionized water to prepare an alkaline source solution (the volume ratio of the alkaline source solution to the cerium source solution is 1.2).
[0124] 3) Dissolve 4 mL of KH560 in a mixture of 50 mL of ethanol and 50 mL of isopropanol to prepare a surface modifier solution (the volume ratio of the surface modifier solution to the cerium source solution is 0.9).
[0125] 4) The alkaline source solution was added dropwise to the cerium source solution using a horizontal flow pump, with the dropping rate controlled at 4 mL / min (0.18 L / min / mol Ce element), the reaction temperature at 95℃, and the stirring rate at 500 r / min to obtain the reaction solution;
[0126] 5) The surfactant solution was added dropwise to the reaction solution obtained in step 4) using a horizontal flow pump. The dropwise addition rate was controlled at 10 mL / min (0.46 L / min / mol Ce element), the stirring rate was 500 r / min, the modification reaction temperature was 75℃, and the modification reaction time was 1 h. After the modification reaction was completed, the cerium dioxide solid was separated by vacuum filtration, washed 4 times by vacuum filtration with ethanol as the liquid phase medium, and vacuum dried at 80℃ for 4 h.
[0127] 6) Using a mixture of 20 mL ethanol and 20 mL ethylene glycol as the dispersed phase, the cerium dioxide solid prepared in step 5) can be transparently dispersed in the above dispersed phase, resulting in an orange transparent cerium dioxide dispersion. A physical image is shown below. Figure 1 As shown, the solid content is 2 wt.% (the volume ratio of cerium dioxide dispersion to cerium source solution is 0.3);
[0128] 7) Using a mixture of 50 mL 1,2-butanediol, 2 mL deionized water and 50 mL isopropanol as a solvent, add 2 g of copper sulfate pentahydrate to prepare a copper source solution (the volume ratio of the copper source solution to the cerium source solution is 0.9).
[0129] 8) 50 mL of cerium dioxide dispersion (cerium dioxide solid content of 2 wt.%) was added dropwise to 102 mL of copper source solution (Cu:Ce atomic ratio of 0.36) using a horizontal flow pump. The dropping rate was controlled at 100 mL / min (4.6 L / min / mol Ce element), and the stirring rate was 500 r / min. After mixing, a solvothermal reaction was carried out at a solvothermal temperature of 180 °C for 20 h. After the solvothermal reaction was completed, the copper cerium oxide solid was separated by vacuum filtration, washed 4 times by vacuum filtration with ethanol as the liquid phase medium, and then vacuum dried at a drying temperature of 80 °C for 4 h.
[0130] 9) Using n-heptane as the dispersed phase, the copper cerium oxide solid prepared in step 8) can be transparently dispersed in the above dispersed phase, resulting in a brown transparent dispersion of copper cerium oxide, as shown in the figure below. Figure 2 As shown, the solid content is 2 wt.%, and no precipitation occurs after standing for 24 months; the dispersion remains transparent and stable.
[0131] The obtained copper-cerium oxide was observed using a transmission electron microscope. Figure 3 It can be seen that the average particle size of the obtained copper cerium oxide particles is 2.3 nm, and the particles are uniformly dispersed. The XRD patterns of cerium dioxide and copper cerium oxide are shown below. Figure 4 As shown in the figure, both the obtained cerium dioxide and copper cerium oxide exhibit the fluorite-type structure of cerium dioxide, with good crystallinity. The addition of copper did not alter the crystal form of cerium dioxide. The EDX spectrum of copper cerium oxide (…) Figure 5 This indicates that copper is uniformly distributed within the cerium dioxide nanoparticles.
[0132] 0.25 g of the above-prepared transparent dispersion of copper cerium oxide in the n-heptane phase (containing 5 mg of copper cerium oxide catalyst) with a solid content of 2 wt% was spin-coated onto a 2.5 cm × 3.5 cm ITO glass plate. The surface modifier was removed by irradiation with an ultraviolet ozone cleaner for 1 hour. The photocatalytic carbon dioxide reduction experiment was carried out in gas-solid mode: the light source was a 300 W xenon lamp with an irradiance of 100 mW / cm². 2 The apparatus was evacuated three times, carbon dioxide was introduced to 0.26 MPa, and 200 μL of deionized water was added. The circulating cooling water temperature was 25 °C, and the magnetic stirring speed was 500 r / min. The hydrogen and oxygen content of the products was detected using a TCD detector (thermal conductivity detector); the methane and carbon monoxide content of the products was detected using an FID detector (flame ionization detector). Figure 6 This is a diagram of the experimental setup. Figure 7 The results show the photocatalytic reduction of carbon dioxide using a gas-solid method with copper-cerium oxide obtained in Example 1. The results indicate that the products are methane, hydrogen, and carbon monoxide, with methane as the main product and a yield of 41 μmol / g / h.
[0133] Example 2
[0134] A method for preparing an oil-soluble monodisperse nano-cerium dioxide catalyst includes the following steps:
[0135] 1) Dissolve 12g of cerium chloride heptahydrate in a mixture of 40mL chloroform, 40mL methanol and 40mL deionized water to prepare a cerium source solution;
[0136] 2) Dissolve 2 mL of triethanolamine in a mixture of 1 mL of benzyl alcohol and 60 mL of deionized water to prepare an alkaline source solution (the volume ratio of the alkaline source solution to the cerium source solution is 0.5).
[0137] 3) Dissolve 1.3g of hexadecylammonium bromide in a mixture of 50mL N,N-dimethylformamide and 50mL deionized water to prepare a surface modifier solution (the volume ratio of the surface modifier solution to the cerium source solution is 0.8).
[0138] 4) Add the alkaline source solution dropwise to the cerium source solution, controlling the dropwise addition rate at 100 mL / min (3.1 L / min / mol Ce element), the reaction temperature at 15℃, and the stirring rate at 500 r / min to obtain the reaction solution;
[0139] 5) The surfactant solution was added dropwise to the reaction solution obtained in step 4) using a horizontal flow pump. The dropwise addition rate was controlled at 2 mL / min (0.06 L / min / mol Ce element), the stirring rate was 500 r / min, the modification reaction temperature was 15℃, and the modification reaction time was 3 h. After the modification reaction was completed, the cerium dioxide solid was separated by centrifugation, washed 5 times by centrifugation with cyclohexane as the liquid phase medium, and then freeze-dried at -5℃ for 30 h.
[0140] 6) Using 5 mL of dichloromethane as the dispersed phase, the cerium dioxide solid prepared in step 5) can be transparently dispersed in the above dispersed phase, resulting in a brown transparent cerium dioxide dispersion, as shown in the image below. Figure 8 As shown, the solid content is 20 wt.% (the volume ratio of cerium dioxide dispersion to cerium source solution is 0.04);
[0141] 7) Using a mixture of 10 mL hexane, 50 mL ethanol and 50 mL toluene as a solvent, add 0.8 g of copper stearate to prepare a copper source solution (the volume ratio of the copper source solution to the cerium source solution is 0.9).
[0142] 8) The 110 mL copper source solution obtained in step 7) was added dropwise to the 5 mL cerium dioxide dispersion obtained in step 6) (cerium dioxide solid content of 20 wt.%) (Cu:Ce atomic ratio of 0.04) using a peristaltic pump at a dropping rate of 5 mL / min (0.15 L / min / mol Ce element). After complete mixing, a solvothermal reaction was carried out at a solvothermal temperature of 130 °C for 48 h. After the solvothermal reaction was completed, the copper-cerium oxide solid was separated by centrifugation, washed four times by centrifugation with tetrahydrofuran as the liquid medium, and spray-dried at a drying temperature of 90 °C for 10 h. Using acetonitrile as the dispersion phase, the prepared copper-cerium oxide solid could be transparently dispersed in the above dispersion phase to obtain a brown copper-cerium oxide transparent dispersion, as shown in the figure. Figure 9 As shown, the solid content is 2 wt.%, and no precipitation occurs after standing for 24 months; the dispersion remains transparent and stable.
[0143] 0.25 g of the above-prepared transparent dispersion of copper cerium oxide in the n-heptane phase (containing 5 mg of copper cerium oxide catalyst) with a solid content of 2 wt% was irradiated with an ultraviolet ozone cleaner for 1 h to remove the surface modifier. Then, it was mixed with 10 mL of deionized water, and a photocatalytic carbon dioxide reduction experiment was conducted in liquid-solid mode: the light source was a 300 W xenon lamp, and the irradiance was 100 mW / cm². 2 The apparatus was evacuated three times, carbon dioxide was purged for 20 minutes, the circulating cooling water temperature was 25°C, and the magnetic stirring speed was 500 r / min. The hydrogen and oxygen content of the products was detected using a gas chromatograph with a TCD detector (thermal conductivity detector); the methane and carbon monoxide content of the products was detected using an FID detector (flame ionization detector). The formic acid, acetic acid, methanol, and ethanol content of the products were detected using liquid chromatography. Figure 10 The results show the photocatalytic reduction of carbon dioxide using the liquid-solid method with copper-cerium oxide obtained in Example 2. The results indicate that the products are formic acid and carbon monoxide, with formic acid being the main product, and the yield is 8 mmol / g / h.
[0144] Example 3
[0145] Example 1 was repeated, except that in step 3), KH560 was replaced with an equal amount of polyethylene glycol-4000; the cerium dioxide prepared in step 5) was well dispersed in the mixture of 20 mL ethanol and 20 mL ethylene glycol used as the dispersed phase in step 6), and the expected copper cerium oxide dispersion could still be obtained subsequently. The results show that changing the type of surface modifier in step 3) from a silane coupling agent to a polyethylene glycol can still yield the expected product.
[0146] Example 4
[0147] Example 1 was repeated, except that in step 3), KH560 was replaced with an equal amount of trimethyloxonium tetrafluoroborate; the cerium dioxide prepared in step 5) was well dispersed in the mixture of 20 mL ethanol and 20 mL ethylene glycol used as the dispersed phase in step 6), and the expected copper cerium oxide dispersion could still be obtained subsequently. The results show that changing the type of surface modifier in step 3) from a silane coupling agent to a fluoroborate still yields the expected product.
[0148] Example 5
[0149] Example 2 was repeated, except that in step 3), hexadecylammonium bromide was replaced with an equal amount of lauric acid; the cerium dioxide prepared in step 5) was well dispersed in the 5 mL dichloromethane used as the dispersed phase in step 6), and the expected copper cerium oxide dispersion could still be obtained subsequently. The results show that changing the type of surface modifier in step 3) from a cationic surfactant to a long-chain alkyl acid still yields the expected product.
[0150] Comparative Example 1
[0151] Example 1 was repeated, except that in step 3), KH560 was replaced with an equal amount of distearate. The results showed that changing the type of surface modifier in step 3) resulted in the cerium dioxide prepared in step 5) not being well dispersed in the dispersion phase of the mixture of 20 mL ethanol and 20 mL ethylene glycol in step 6). The cerium dioxide nanoparticles precipitated in the dispersion phase, so the expected copper cerium oxide dispersion could not be obtained subsequently.
[0152] Comparative Example 2
[0153] Example 2 was repeated, except that in step 8), the cerium dioxide dispersion was replaced with an equal amount of zirconium dioxide dispersion (both 5 mL, the dispersed phase being dichloromethane, the zirconium dioxide solid content being 20 wt.%, and the zirconium dioxide particle size being 3 nm). The resulting mixture was a mixture of zirconium dioxide and cuprous oxide nanoparticles, and its transmission electron microscopy image and corresponding photograph are shown below. Figure 11 As shown in the diagram. This comparative experiment demonstrates that when other types of metal oxides are used instead of cerium dioxide, copper oxide is easily formed when copper is added.
[0154] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is impossible to exhaustively list all embodiments here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a sub-nanometer-scale monodisperse copper-cerium oxide catalyst dispersion, characterized in that, The sub-nanometer copper cerium oxide is formed by uniformly distributing copper elements within cerium dioxide particles, and coating the surface of the sub-nanometer monodisperse copper cerium oxide particles with a surface modifier layer, which is then uniformly dispersed in a liquid medium to form a transparent dispersion. The transparent dispersion contains 0.005 wt.% to 60 wt.% of sub-nanometer copper cerium oxide, with a one-dimensional particle size of 0.5 nm to 3 nm; the Cu:Ce molar ratio is 0.0001 to 3:
1. The preparation method includes the following steps: 1) Prepare a cerium source solution by adding a cerium source to water, an organic solvent, or a mixture of water and an organic solvent; 2) Prepare an alkali source solution by adding an alkali source to water, an organic solvent, or a mixture of water and an organic solvent; 3) Prepare a surface modifier solution by adding a surface modifier to water, an organic solvent, or a mixture of water and an organic solvent; 4) Mix the cerium source solution from step 1) with the alkali source solution from step 2), and continue the reaction after mixing; 5) Mix the surface modifier solution with the mixture from step 4), and continue the modification reaction after mixing. After the reaction, perform solid-liquid separation, and wash and dry the separated cerium dioxide solid. 6) Using water, organic solvent, or a mixture of water and organic solvent as the dispersed phase, the washed and dried cerium dioxide solid can be transparently dispersed in the dispersed phase to obtain a transparent cerium dioxide dispersion. 7) Prepare a copper source solution by adding a copper source to water, an organic solvent, or a mixture of water and an organic solvent; 8) Mix the transparent cerium dioxide dispersion from step 6) with the copper source solution from step 7) and carry out a solvothermal reaction. After the reaction, perform solid-liquid separation, wash and dry the separated copper cerium oxide solid, and disperse the washed and dried copper cerium oxide solid in a liquid medium to obtain the product sub-nanometer monodisperse copper cerium oxide catalyst dispersion. In step 3), the surface modifier is selected from one or more of the following substances: butyric acid, octanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, oleic acid, linoleic acid, [3-(methacryloyloxy)propyl]trimethoxysilane, γ-glycidyl etheroxypropyltrimethoxysilane, (3-aminopropyl)triethoxysilane, (3-mercaptopropyl)trimethoxysilane, hexadecyl ammonium bromide, polyethylene glycol-200, polyethylene glycol-4000, polyethylene glycol-10000, trimethyloxonium tetrafluoroborate, triethyloxonium tetrafluoroborate, nitrosotetrafluoroborate, tribenzylcarbium tetrafluoroborate, and ammonium fluoroborate. In step 4), the reaction temperature is 10~150℃ and the reaction time is 0~3 h; in step 8), the solvothermal reaction temperature is 80~260℃ and the solvothermal time is 2 h~96 h.
2. The method according to claim 1, characterized in that, In step 1), the cerium source is selected from one or more of the following substances: cerium fluoride, cerium iodide, cerium bromide, anhydrous cerium sulfate, cerium sulfate tetrahydrate, anhydrous cerium chloride, cerium chloride heptahydrate, cerium nitrate hexahydrate, cerium oxalate hydrate, cerium (III) carbonate hydrate, and cerium (III) acetate hydrate. In step 1), the organic solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol, glycerol, benzyl alcohol, toluene, tetrahydrofuran, dichloromethane, chloroform, N,N-dimethylformamide, and dimethyl sulfoxide. In step 2), the alkali source is selected from one or more of the following substances: sodium hydroxide, potassium hydroxide, calcium hydroxide, ammonia, tetramethylammonium hydroxide, tetraethylammonium hydroxide, triethylamine, and triethanolamine; In step 2), the organic solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol, glycerol, benzyl alcohol, toluene, tetrahydrofuran, dichloromethane, chloroform, N,N-dimethylformamide, dimethyl sulfoxide, and methyl isobutyl ketone. In step 3), the organic solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol, glycerol, benzyl alcohol, toluene, tetrahydrofuran, dichloromethane, chloroform, N,N-dimethylformamide, dimethyl sulfoxide, and methyl isobutyl ketone. In step 6), the organic solvent is selected from one or more of the following substances: formamide, N,N-dimethylformamide, methanol, ethanol, ethylene glycol, acetonitrile, dimethyl sulfoxide, tetrahydrofuran, toluene, benzene, benzyl alcohol, cyclohexane, n-hexane, n-heptane, dichloromethane, chloroform, white oil, naphtha, castor oil, diesel oil, methyl isobutyl ketone, methyl methacrylate, 3-phenoxybenzyl acrylate; In step 7), the copper source is selected from one or more of the following substances: copper gluconate, copper acetylacetone, copper fluoroborate, copper citrate, copper acetate monohydrate, copper isooctanoate, anhydrous copper acetate, basic copper carbonate, copper tartrate (II) hydrate, copper oxalate, copper acetate monohydrate, butyrate, copper stearate, anhydrous copper sulfate, copper sulfate pentahydrate, basic copper sulfate, anhydrous copper chloride, copper chloride dihydrate, and copper nitrate trihydrate; the organic solvent is selected from one or more of the following substances: oleic acid, linoleic acid, oleylamine, methanol, ethanol, isopropanol, toluene, benzyl alcohol, cyclohexane, n-hexane, and 1,2-butanediol.
3. The method according to claim 1, characterized in that, In step 1), the concentration of the cerium source solution is 0.01 wt.%~60 wt%; in step 2), the concentration of the alkali source solution is 0.1 wt.%~50 wt.%; in step 3), the concentration of the surface modifier solution is 0.1 wt.%~80 wt.%; in step 4), the volume ratio of the alkali source solution to the cerium source solution is 0.01~6:1; in step 4), the mixing method of the cerium source solution and the alkali source solution is: adding the cerium source solution to the alkali source solution at a certain flow rate, or adding the alkali source solution to the cerium source solution at a certain flow rate; the stirring rate is 200~800 r / min; In step 5), the mixing method of the mixture and surfactant solution in step 4) is as follows: the surface modifier solution is added to the mixture in step 4) at a certain flow rate; the stirring rate is 200~800 r / min; and the volume ratio of the mixture to the surfactant solution is 0.1~50:
1. Step 5) The liquid medium used for washing is selected from one or more of the following substances: methanol, ethanol, isopropanol, toluene, cyclohexane, n-hexane, acetone, benzyl alcohol, tetrahydrofuran, dichloromethane, and trichloromethane; the number of washing cycles is 2 to 5; the drying method is one or more of the following: freeze drying, vacuum drying, atmospheric pressure evaporation, rotary vacuum evaporation, forced air drying, infrared irradiation, and spray drying. In step 8), the mixing method of the cerium dioxide transparent dispersion and the copper source solution is as follows: the cerium dioxide transparent dispersion is added to the copper source solution at a certain flow rate; the liquid phase medium used for washing is selected from one or more of the following substances: methanol, ethanol, isopropanol, toluene, cyclohexane, n-hexane, acetone, benzyl alcohol, tetrahydrofuran, dichloromethane, and trichloromethane; the number of washing cycles is 2 to 5; the drying method is one or more of the following: freeze drying, vacuum drying, atmospheric pressure evaporation, rotary vacuum evaporation, forced air drying, infrared irradiation, and spray drying. In step 8), the molar ratio of cerium dioxide to Cu:Ce in the copper source is 0.0001~3:
1.
4. The method according to claim 1, characterized in that, In step 1), the concentration of the cerium source solution is 0.1 wt.% to 50 wt.%; in step 2), the concentration of the alkali source solution is 0.5 wt.% to 40 wt.%; in step 3), the concentration of the surfactant solution is 0.5 wt.% to 40 wt.%; in step 4), the volume ratio of the alkali source solution to the cerium source solution is 0.02 to 5:1; in step 8), the molar ratio of cerium dioxide to Cu:Ce in the copper source is 0.005 to 2.7:
1.
5. The method according to claim 1, characterized in that, In step 4), the reaction temperature is 15~95℃ and the reaction time is 0~2.5 h; in step 8), the solvothermal reaction temperature is 120~250℃ and the solvothermal time is 2 h~72 h.
6. The sub-nanometer monodisperse copper cerium oxide catalyst dispersion prepared according to any one of claims 1-5.
7. The application of the sub-nanometer-scale monodisperse copper cerium oxide catalyst dispersion prepared according to any one of claims 1-5, wherein the catalyst is used as a photocatalytic carbon dioxide reduction catalyst.
8. According to the application of claim 7, the photocatalytic carbon dioxide reduction system uses a gas-solid mode or a liquid-solid mode; in the gas-solid mode, the prepared sub-nanometer-scale monodisperse copper-cerium oxide catalyst nanodispersion is loaded onto a support, and the surfactant layer encapsulated by the nano-copper-cerium oxide catalyst is removed by ultraviolet ozone photo-cleaning machine, with deionized water as a sacrificial agent and carbon dioxide as a reactant, and the reaction is carried out under visible light irradiation; in the liquid-solid mode, the sub-nanometer-scale monodisperse copper-cerium oxide catalyst nanodispersion is directly added to the reaction system, a sacrificial agent is added, and the reaction is carried out under visible light irradiation with carbon dioxide as a reactant.
9. In the application according to claim 8, the carrier in the gas-solid mode is one or more of ITO glass, FTO glass, ordinary glass, hydrophilic carbon cloth, and hydrophobic carbon cloth; The loading method in the gas-solid mode is one or more of the following: impregnation, spin coating, scraping, and spraying. In the gas-solid mode, the photocatalytic carbon dioxide reduction products are one or more of carbon monoxide, hydrogen, methane, ethylene, and ethane. In the liquid-solid mode, the sacrificial agent is one or more of triethanolamine, triethylamine, sodium N,N-dimethylformamide sulfide, sodium sulfite, and lactic acid; In the liquid-solid mode, the photocatalytic carbon dioxide reduction products are one or more of carbon monoxide, hydrogen, methane, ethylene, ethane, formic acid, acetic acid, methanol, and ethanol.
Citation Information
Patent Citations
Trivalent rare earth doped cerium dioxide supported metal catalyst as well as preparation method and application thereof
CN116966911A
Catalyst for preparing low-carbon olefins by catalytic cracking of hydrocarbons, and preparation method thereof
CN111203225A
Oil-soluble monodisperse nano cerium dioxide catalyst as well as preparation method and application thereof
CN111434379A